Optimization of False Alarm Rate and Misdetection Rate for a Desired Threshold Voltage in Cooperative Communication - SATISH KUMAR GANNAMANENI; JIBENDU SEKHAR ROY (Jordanian Journal of Computers and Information Technology)
Cooperative communication system (CCS) involves collaboration among sensor nodes to transmit data more effectively, especially in scenarios with limited resources or challenging environmental conditions. Optimizing the total error rate (TER) for cooperative communication in wireless sensor networks (WSN) is a critical task to enhance the reliability and efficiency of data transmission. The link quality of a WSN can be improved by cooperative relaying with a relatively low TER. In this paper, real-coded genetic algorithm (RGA) and particle swarm optimization (PSO) are used in WSN to reduce TER. The number of nodes are varied from 1 to 16, SNR is varied from 0 dB to 20 dB, threshold is varied from 25 mV to 35 mV and mutation rate is 0.1. Minimum TER is obtained for a threshold of 25 mV to 35 mV compared to TER obtained without optimization. The optimization method provides significant improvements to achieve the desired threshold voltage with minimum false alarm rate and misdetection rate which enhances the overall performance of the CCS in WSNs. [JJCIT 2025; 11(1.000): 73-84]